Image quality and contrast agent exposure in cardiac computed tomography angiography prior to transcatheter aortic valve implantation procedures using different acquisition protocols - Hofmann, Nina; Schütz, Moritz; Bekeredjian, Raffi; Pleger, Sven Torsten; Chorianopoulos, Emmanuel; Giusca, Sorin; André, Florian; Gitsioudis, Gitsios; Schlett, Christopher L.; Kauczor, Hans-Ulrich; Katus, Hugo; Korosoglou, Grigorios (European journal of radiology open, 2017)
Background: ECG-gated cardiac computed tomography angiography (CCTA) has found widespread use for prosthesis sizing before transcatheter aortic valve implantation (TAVI). However, still little data exists on the optimal scan-strategy in such patients. We hypothesized that prospectively triggered CCTA can enable the visualization of aortic valve structures and peripheral arteries with lower radiation and contrast agent exposure in patients considered for TAVI compared to retrospectively gated protocols. Methods: All studies were performed using a 256 multi-detector single source CT (iCT Philips, Best, Netherlands). With the prospective protocol the whole volume from the heart to the iliofemoral arteries scanned using prospective triggering. With the retrospective protocol a first retrospectively gated scan was performed for the heart and the iliofemoral part was subsequently scanned using a second non-triggered scan. Image quality was assessed semi-quantitatively and signal-to-noise- (SNR) and contrast-to-noise-ratios (CNR) were obtained for all scans.Results: Prospective CCTA was performed in 74 and in 34 patients, respectively using non-tailored and BMI adapted scans, whereas retrospective CCTA was performed in 57 patients. Prospective scans required lower contrast agent administration compared to retrospective scans (71±8mL versus 91±15mL, p<0.01) and resulted in lower radiation exposure (26±7mSv for retrospective versus 15±3mSv for non-tailored prospective versus 8±4mSv for BMI-adapted prospective scans, p<0.01). Visual image quality was better for the evaluation of aortic valve structures and similar for the assessment of iliofemoral anatomy with prospective versus retrospective scans. In addition, contrast density, SNR and CNR were higher in the ascending aorta with prospective versus retrospective CCTA (434±98HU versus 349±112HU; 35±14 versus 24±9 and 31±11 versus 16±7, p<0.001 for all). Subsection analysis by heart rate groups demonstrated that both image quality and CNR were significantly higher in patients with prospective versus retrospective CCTA, irrespective of the heart rate during image acquisition. Conclusion: Prospectively triggered CCTA allows for improved visualization of aortic valve structures and peripheral arteries in patients scheduled for TAVI with simultaneously reduced contrast agent dose and radiation exposure. Therefore, this acquisition mode seems to be the preferred for the evaluation of patients considered for TAVI.